Building Soil Potassium and Phosphorus in a Low‐Testing Fescue Hay Field. Issue 1 (1st April 2014) - Stevens, Gene; Hefner, Steven; Kurtz, Ian; Dunn, David; Rhine, Matt; Heiser, Jim
Abstract : A fescue hay field in the Ozark Highlands received phosphorus (P) and potassium (K) fertilizer to build up soil test levels above target levels. Fertilizer rates were applied to build the soil test P and K levels in one, four, or eight years. Averaged across eight years, hay yields were not significantly different between build‐up timings. However, compared to the untreated control, hay yield and quality were significantly increased by applying P and K.